AN OVERVIEW OF COMMONLY DIAGNOSED PAROTID GLAND - Krishna Malay, Kausalyah; Saravanan; Duraisawamy, Revathy; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
The parotid gland is a major salivary gland in humans. It is a bilateral structure, and the largest of the three major salivary glands. It is wrapped around the mandibular ramus, and secretes saliva through Stensens duct (or parotid duct) into the oral cavity, to facilitate mastication and swallowing and to begin the digestion of starches. Additionally, the mucosa of the upper aero digestive tract is lined by hundreds of small, minor salivary glands. The major function of the salivary glands is to secrete saliva, which plays a significant role in lubrication, digestion, immunity, and the overall maintenance of homeostasis within the human body. The duct pierces the buccinator muscles, then opening up into the oral cavity on the inner surface of the cheek, usually opposite the maxillary second molar. The parotid papilla is a small elevation of tissue that marks the opening of the parotid duct on the inner surface of the cheek.